Implementasi Strategi Pembelajaran Afektif pada Mata Pelajaran Akidah Akhlak untuk Meningkatkan Self Control Siswa di MTS Muhammadiyah 02 Purbalingga - Umi Kulsum; Fauzi Fauzi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to analyze the implementation of affective learning strategies in Akidah Akhlak subjects to enhance students' self-control at MTs Muhammadiyah 02 Purbalingga. Affective learning strategies focus on character development through the inculcation of religious values such as patience, honesty, and discipline, aimed at helping students manage their emotions, thoughts, and behavior in daily life. The research employed a qualitative method with a descriptive approach. Data were obtained through in-depth interviews with Akidah Akhlak teachers, the principal, and students, as well as classroom observation. Data analysis was conducted using thematic coding to identify patterns in the implementation of affective learning strategies and their impact on students' self-control. The findings indicate that the implementation of affective learning strategies is carried out through five main stages: receiving, responding, valuing, organization, and characterization. Each stage involves structured approaches, such as using inspirational stories from the Qur'an and Hadith, group discussions, value reflections, and case study simulations. These strategies successfully enhanced students' self-control, particularly in emotional regulation, wise decision-making, and consistent behavior aligned with Islamic values. This study concludes that affective learning strategies play a vital role in improving students' self-control. Systematic and collaborative implementation can assist madrasahs in producing a generation that is faithful, knowledgeable, and morally upright, in line with the vision of Islam.